Awareness and Utilisation of Primary Healthcare to Reduce Emergency Department Overcrowding in Saudi Arabia - Atheer Alotaibi; Bandar Alotaibi; Dania Farooq (The Journal of Medicine, Law & Public Health, 2023)
Background